FRI0480-HPR Effects of an acute aerobic exercise bout on plasma oxidant and antioxidant levels in rheumatoid arthritis patients. (23rd January 2014) - Tuna, Z.; Düger, T.; Güzel, N.; Haznedaroğlu, S.
Abstract : Background: Exercise can stimulate the oxidative metabolism and potentially affect oxidants and antioxidants. Meanwhile, oxidative stress also plays an important role in the pathobiology of rheumatoid arthritis (RA). Since the benefits of different exercise types in RA are well-established, the effects of an acute aerobic exercise bout on the plasma oxidant and antioxidant levels may be clinically relevant. Objectives: This study aimed to assess the effects of an acute submaximal aerobic exercise bout on plasma malondialdehyde (MDA) and total sulfhydrile groups (RSH) levels in RA patients. Methods: Sixteen RA patients in remission and 10 age-matched healthy volunteers participated in the study. The patients were confirmed to have no contraindications to take part in the study by a rheumatologist. The exercise intensity was determined by using heart rate which was followed during the whole test by a polar telemeter. All participants walked on the treadmill at the intensity of %60-75 of maximal heart rate for 30 minutes. Blood samples were obtained before, after and 24 hours later the test. Plasma MDA and RSH levels were assessen in the samples. Results: Both groups reached similar heart rates (p>0.05) during the test but test speed of patients were significantly lower (p<0.05). Plasma MDA levels decreased after exercise in both groups (p<0.05) with a greater decrements in the RA patients (p<0.01). However, 24 hours later only control group returned to baseline levels compared to after-exercise levels (p<0.05). Plasma RSH levels increased slightly with exercise in both groups (p>0.05). Conclusions: These results indicated that an acute bout of aerobic exercise decreased the plasma oxidant levels in RA patients. Therefore, such an acute aerobic exercise model could exert an antioxidant effect partly and this effect is highly preserved for longer in RA patients. Based on those results, moderate aerobic exercise like walking is safe in RA patients with additional benefits on the oxidative metabolism. References: Banerjee, AK, Mandal, A, Chanda, D, Chakraboti, S. (2003) Oxidant, antioxidant and physical exercise. Molecular and Cellular Biochemistry, 253, 307-12. Kamanlı A, Nazıroğlu M, Aydilek N, Hacıevliyagil C. (2004) Plasma lipid peroxidation and antioxidant levels in patients with rheumatoid arthritis. Cell Biochemistry and Function, 22, 53–7. Hurkmans, E, van der Giesen, FJ, Vliet Vlieland, TPM, Schoones, J, Van den Ende, ECHM. (2009) Dynamic exercise programs (aerobic capacity and/or muscle strength training in patients with rheumatoid arthritis. Cochrane Database of Systematic Reviews, Issue 4 Disclosure of Interest: None Declared